Effects of a 7-day step taper, training cessation, and retraining on lower body physical and morphological aspects in elite female ice hockey players - Nishiumi, Daichi; Yamashita, Daichi; Kurokawa, Takanori; Hirase, Naoki; Wakamiya, Kazuki; Mujika, Iñigo; Hirose, Norikazu (Frontiers in Sports and Active Living, 2025)
PurposeThis study investigated the effects of a 7-day step taper before a national championship, followed by 2 weeks of training cessation and 2 weeks of retraining on lower body physical and morphological aspects.MethodsSeven elite female ice hockey players (age: 23 ± 4 years) participated in six testing sessions: two baseline sessions, one pre-championship (after taper), one after a 2-week training cessation, and two following retraining (after 1 week and after 2 weeks). Assessments included body composition, vastus lateralis muscle architecture (muscle thickness, pennation angle, fascicle length), and lower body vertical force–time metrics [countermovement jump (CMJ), squat jump (SJ), and loaded SJ]. During the tapering period, training duration was reduced by 35%. During retraining, participants performed three weekly sessions of fast eccentric squats, with 4 sets of 8 repetitions per session, gradually increasing intensity from 45.5% to 63.5% of estimated 1RM.ResultsTapering did not affect any of the lower body physical and morphological measures. Training cessation induced declines in braking rate of force development (13.1%, p < 0.05), braking peak force during CMJ (5.5%, p < 0.05), and muscle mass (3.6%, p = 0.03). All metrics returned to post-taper values within 1 week of retraining.Conclusions2 weeks of training cessation induced minor declines in eccentric muscle performance, but recovered within 1 week of retraining. This study provides valuable insights for practitioners in designing effective peaking, off season and retraining programs in female ice hockey.